The use of ultrasonography in the diagnosis and management of Acute Kidney Injury and other forms renal dysfunction in the paediatric population: Systematic review protocol - Gontse Leballo; Nabeela Arbee-Kalidas; Moses Mogakolodi Kebalepile; Palesa Motshabi Chakane (PLoS ONE, 2025)
Background Acute kidney injury remains one of the most prevalent complications in hospitalised patients, with an especially high incidence in the paediatric population. Its diverse pathophysiological aetiologies present significant challenges in its clinical diagnosis. Relying solely on serum creatinine levels and urine output measurements for diagnosis has been shown to be inadequate, particularly for early detection of the disease. The wide range of disease manifestations highlights the importance of exploring diagnostic techniques that can identify patients at risk before disease progression occurs, thereby allowing for the implementation of timely corrective measures. Point-of-care ultrasound is a valuable technique with the potential to aid in the early identification of at-risk patients. Objective To describe ultrasound parameters associated with the development of acute kidney injury or renal dysfunction in the hospitalised paediatric patient, and to examine their association with its development. This will include an analysis of the specific ultrasound features that may predict or be associated with the occurrence of acute kidney injury, as well as their potential role in identifying at-risk paediatric patients, facilitating timely interventions to mitigate further kidney damage. Methods A systematic review of existing literature will be performed to assess ultrasound modalities currently associated with the diagnosis of acute kidney injury in the paediatric population. The protocol for this review has been registered with PROSPERO (CDR42024547614) and was developed in accordance with the guidelines set forth by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA). A comprehensive search of scientific literature will be conducted across PubMed, Scopus, Cochrane Library, and CINAHL databases. The data search will be performed independently by the primary researchers (GL and NA), with any disagreements resolved by the third and fourth researchers (MK, PMC). The COVIDENCE Systematic Review Software® 2024 will be utilised for article exportation, review, and data extraction. The QUADAS-2 tool will be applied to assess the risk of bias in the diagnostic accuracy of the studies included in the review. Conclusion This protocol outlines a systematic review designed to evaluate the application of ultrasonography in identifying paediatric patients at risk of developing acute kidney injury and other forms of renal dysfunction. The review will critically assess the effectiveness of ultrasound techniques, including point-of-care ultrasound, in identifying acute kidney injury in children, with a particular emphasis on early detection. The findings from this review will contribute to a deeper understanding of the role of ultrasonography in clinical practice, with the potential to improve patient outcomes through earlier intervention. The ultrasound techniques identified, including Doppler imaging and flow measurements, will be employed in a subsequent prospective study within the paediatric population to evaluate their role, sensitivity, and accuracy.